The impact of tariffs and price premiums of locally manufactured products on global manufacturers' sourcing strategies - Chen, Kanglin; Wang, Xin; Niu, Baozhuang; Chen, Ying‐Ju (Production and Operations Management, 2022)
The past decade has seen significant pressure to return manufacturing to developed countries. Such movements call for import tariffs to be raised and consumers' valuation of products made from locally sourced components increased. These factors are believed to stimulate firms operating in a single market to source components locally. However, it is not clear that they are equally effective for multinational firms that produce and sell products in multiple markets. To enrich the understanding of this issue, we build a game‐theoretical model to analyze the sourcing decisions of a global manufacturer that maintains production sites and sells products in both domestic and foreign markets in a competitive environment. The firm can choose either to source components from suppliers located in the same markets as the manufacturing sites to gain tariff savings and a price premium from consumers' higher valuation, or to source all components from a single foreign supplier to obtain a lower sourcing cost. We find that the structure of the global supply chain plays a critical role in the firm's sourcing strategy. Consumers' higher valuation of locally manufactured goods always promotes local sourcing. Raising tariffs, however, might backfire and discourage local sourcing because of the firm's global supply chain structure and the foreign supplier's strategic response to higher tariffs. Finally, local sourcing may reduce the consumer surplus even though consumers place a higher value on locally manufactured goods. This paper sheds light on recent movements to return manufacturing to developed countries and demonstrates the importance of taking the manufacturer's global supply chain structure and vertical interaction with suppliers into account.